Body image in relation to self-esteem in a sample of spanish women with early-stage breast cancer - Manos, Dimitra; Sebastián, Julia; Bueno, Maria José; Mateos, Nuria; Torre, Alejandro de la (Psicooncología, 2005)
Aim: Women diagnosed and surgically treated for early-stage breast cancer were studied to determine the influence that sociodemographic variables, type of surgery, amount of social support, and quality of life had on their body image and self-esteem. Method: Subjects n=54; Measures: Self Esteem Scale (Rosenberg, 1965), Body Image Questionnaire (authors´article) and E.O.R.T.C. (Quality of life) (Aaronson et al, 1988) Result and conclusions: Analyses of variance showed that married women reported a more positive body image than non married women, and so did women with a lumpectomy versus those with a mastectomy. These variables did not relate significantly to the patients’ self-esteem, which in turn was found to be higher in women aged 43-55 years old when compared to younger women. Correlational analyses revealed a significant negative correlation between the deterioration of quality of life after surgery and both body image and